International knowledge spillovers: The benefits from employing immigrants - Jürgen Bitzer; Erkan Gören; Sanne Hiller (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper explores the role of immigrant employees for a firm's capability to absorb international knowledge. Using matched employer-employee data from Denmark for the years 1999 to 2009, we are able to show that non-Danish employees contribute significantly to a firm's economic output through their ability to access international knowledge. The immigrants' impact increases if they come from technological advanced countries, have a high educational level, and are employed in high skilled positions. However, the latter does not hold for immigrant managers.
Keywords: D20; J82; L20; O30; 330; R&D Spillovers; Absorptive Capacity; Firm-Level Analysis; Foreign Workers; Immigrants